2022
DOI: 10.3389/fpubh.2022.871923
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Feeding Styles and Child Appetitive Traits: Direction of Effects in Hispanic Families With Low Incomes

Abstract: Feeding styles of parents have been associated with dietary quality/intake and weight outcomes; however, much of the research to date has been cross sectional and the direction of influence unclear. This prospective longitudinal study evaluated the direction of effects between feeding styles and child appetitive traits over time in a sample of 129 Hispanic parent/child dyads that participated in a larger study. Data analyzed for the current study were collected when the children were 4–5 years old and again at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
2
1
Order By: Relevance
“…This highlights the need for future research to examine factors that contribute to controlling feeding among infants, especially in the case of pressure given our results support a unidirectional parent-driven effect. The longitudinal stability of infant food responsiveness in the current study was lower than previously reported in studies conducted with children 2 years and older ( 27 , 30 , 47 ). Taken together, interventions that target maternal feeding after the 1st year may have limited success in modifying appetitive behaviors to reduce later obesity risk ( 47 ).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This highlights the need for future research to examine factors that contribute to controlling feeding among infants, especially in the case of pressure given our results support a unidirectional parent-driven effect. The longitudinal stability of infant food responsiveness in the current study was lower than previously reported in studies conducted with children 2 years and older ( 27 , 30 , 47 ). Taken together, interventions that target maternal feeding after the 1st year may have limited success in modifying appetitive behaviors to reduce later obesity risk ( 47 ).…”
Section: Discussioncontrasting
confidence: 95%
“…A recent systematic review and meta-analysis that included 14 prospective longitudinal studies examining relations between parental controlling feeding and child appetitive behaviors revealed two significant pooled effects (26): higher child food responsiveness predicted increases in restrictive as well as instrumental feeding (i.e., the use of food as a reward). In line with these results, a recent study showed that higher child food responsiveness at 4-5 years predicted an authoritarian feeding style marked by high levels of parental control when children were aged 7-9 years (27). Although pooled analyses were not conducted for longitudinal associations between pressure to eat and food responsiveness or between emotional feeding and food responsiveness in the aforementioned systematic review due to a limited number of studies, 3 of the 14 prospective studies reported significant longitudinal effects.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, these strategies may be protective for children who have less inhibitory control and/or are more responsive to their environment [70]. There is an emerging body of research that suggests that the feeding relationship between caregiver and child is bi-directional, with children shaping their parents' use of feeding practices [71][72][73]. Indeed, an important characteristic of responsive parenting is that the caregiver's responses should be contingent on their child's cues and behavior [74][75][76].…”
Section: Discussionmentioning
confidence: 99%